2017
DOI: 10.1063/1.4973585
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoidal current collector for lithium-ion battery

Abstract: In the current study, we investigated sigmoidal current collector in lithium-ion battery (LIB). Traditionally, the active material in an LIB electrode is coated on a flat current collector. By rendering the current collector sigmoidal-shaped, cracking and debonding of active material layer could be promoted, which would considerably increase the internal impedance, as the LIB is mechanically abused, beneficial to thermal-runaway mitigation. The energy absorption capacity is also improved, enabling multifunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Plenty of efforts are made to design low resistance electrode in these aspects, such as current collector (CC) optimization (Wang et al, 2017b,c;Lin et al, 2018a;Feng et al, 2019a), electrode porous structure design (Chen et al, 2016a;Fritsch et al, 2018), and so on. Although most works on CC optimization focuses on ESR reduction and rate performance improvement by surface roughening (Wang et al, 2017c) or 3D metal foam adopting (Fritsch et al, 2018), while it also has direct effect on the safety performance. Qiao's group found that upon external loading, heat generation of damaged LIB is heavily dependent on the failure mode of the CC, therefore, by efficient surface notch design on the CC, short circuit of the cell could be effectively eliminated (Wang et al, 2017b).…”
Section: Low Resistance Electrodementioning
confidence: 99%
“…Plenty of efforts are made to design low resistance electrode in these aspects, such as current collector (CC) optimization (Wang et al, 2017b,c;Lin et al, 2018a;Feng et al, 2019a), electrode porous structure design (Chen et al, 2016a;Fritsch et al, 2018), and so on. Although most works on CC optimization focuses on ESR reduction and rate performance improvement by surface roughening (Wang et al, 2017c) or 3D metal foam adopting (Fritsch et al, 2018), while it also has direct effect on the safety performance. Qiao's group found that upon external loading, heat generation of damaged LIB is heavily dependent on the failure mode of the CC, therefore, by efficient surface notch design on the CC, short circuit of the cell could be effectively eliminated (Wang et al, 2017b).…”
Section: Low Resistance Electrodementioning
confidence: 99%
“…It was proposed that, as cylindrical battery cells are placed in parallel and confined by regular walls [8,9], a disintegrable structure can be formed, which provides sufficient flexibility to protect battery cells in a vehicle collision. A number of studies were performed on battery safety and robustness at the cell level [10][11][12][13][14][15]. Functional current collector (FCC) [10][11][12] was developed to isolate the damaged areas in a mechanically abused battery cell, which significantly decreased the heat generation rate.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies were performed on battery safety and robustness at the cell level [10][11][12][13][14][15]. Functional current collector (FCC) [10][11][12] was developed to isolate the damaged areas in a mechanically abused battery cell, which significantly decreased the heat generation rate. Thermally sensitive binder (TSB) [13,14] was developed to reduce the electronic conductivity once the battery was overheated, and thermal runaway retardant (TRR) [15] was employed to lower the ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently investigated thermal-runaway mitigation mechanisms triggered by mechanical processes. For instance, adding a small amount of damage initiators into electrode [19][20][21] could promote widespread damages in electrodes under impact. The significant increase in internal impedance could suppress the ISC formation.…”
Section: Introductionmentioning
confidence: 99%